COMPARATIVE PHRASEOLOGICAL UNITS IN ENGLISH - Begizova Madina Karimovna (Western European Studies, 2024)
This article explores the structural and semantic nuances of comparative idioms in English, focusing on various types of comparisons between two entities. By analyzing their construction and meaning, this study aims to deepen our understanding of how language encapsulates and expresses comparative concepts through idiomatic expressions. Through a systematic examination of these idiomatic comparisons, this research contributes to the broader field of linguistic studies by shedding light on the intricate ways in which language reflects and shapes comparative thought.
Keywords: idiom; structure; semantics; symbol